The Clear Pathway of the Constitutional Court's Decision on Adherents of Belief In Indonesia - Wahanisa, Rofi; Mukminto, Eko; Al Fikry, Ahmad Habib; Rachmawati, Fairus Augustina (Faculty of Law, University of Jember, Indonesia, 2024)
The conception of state of law holds the principles of human rights protection and independent as well as unbiased justice in its implementation. The Constitutional Court has a significant role in reviewing constitutionality under the constitution as stipulated in Article 24C paragraph (1) of the Constitution. The Constitutional Court's functions result in final, binding decisions. Judges play a crucial role in implementing impartiality and upholding laws in society. This notion corresponds to Article 5 paragraph (1) of the Law of Judicial Power and the theory of progressive law which view that laws are established for human life. The objectives of this article is: (i) pinpoint the functions of the Constitutional Court in reviewing the Law of Civil Administration; and (ii) uncover the implications of the Constitutional Court Decision Number 97/PUU-XIV/2016. The writer used a normative legal research. The results indicate that (i) in reviewing the Law of Civil Administration the Constitutional Court serves its functions as a constitutional guard, constitutional interpreter, human rights protector, and democracy protector. First, in reviewing a quo law the judges’ considerations are based on the 1945 Constitution as the realization of upholding the constitution. Second, as a constitutional interpreter, the judges interpret religions and beliefs are an integral entity. Third, granting the request of reviewing a quo law is considered as a concrete manifestation of fulfilling and protecting human rights, in this case native-faith followers. Fourth, the request granted provides a clear pathway for acknowledging the identity of native-faith followers so that they can freely practise their faith. (ii) The decision of a quo has massive implications for society and leads to the establishment of laws as a tool of social engineering. Recognizing native-faith followers in civil administration establishes a new norm, ensuring their rights are implemented and fulfilled. KEYWORDS: State of Law, Constitutional Court Decision, and Native Faith.